Dissociating what and when of intentional actions - Krieghoff, Veronika; Brass, Marcel; Prinz, Wolfgang; Waszak, Florian (Frontiers in Human Neuroscience, 2009)
Recent brain imaging research revealed that internally guided actions involve the fronto-median wall, in particular the preSMA and the rostral cingulate zone (RCZ). However, a systematic decomposition of different components of intentional action is still lacking. We propose a new paradigm to dissociate two components of internally guided behaviour: Which action to perform (selection component) and when to perform the action (timing component). Our results suggest a neuro-functional dissociation of intentional action timing and intentional action selection. While the RCZ is more strongly activated for the selection component, a part of the superior medial frontal gyrus (SFG) is more strongly activated for the timing component. However, in a post-hoc conducted signal-strength analysis we did also observe an interaction between action timing and action selection, indicating that decisional processes concerning action timing and action selection are not completely dissociated but interdependent. Altogether this study challenges the idea of a unitary system supporting voluntary action and instead suggests the existence of different neuranatomically dissociable subfunctions.